PENINGKATAN INTERAKSI SOSIAL ANAK MELALUI PERMAINAN SCRABBLE - Musrifah, Nika; Mardiyati, Siti; Djannah, Wardatul (Universitas Sebelas Maret, 2013)
The purpose of this study was to determine the effectiveness of the scrabble games to the development of social interactions with the peer group of a elementary school students in Temanggung. This research was pre-experimental design. The subject of the research were 38 elementary school students. Based on the result of hypothesis, it is known that there are development of social interactions with peer group before and after treatment by scrabble games that is tcount=4,105 compared with ttable=1,68 or tcount>ttable (p value 0,000<0,05). The result of the research that scrabble games is efective to develop the social interactions with peer group in Elementary School students.